Kenya Economic Update, April 2020 : Turbulent Times for Growth in Kenya -- Policy Options during the COVID-19 Pandemic - World Bank (World Bank, Washington, DC, 2020)
The COVID-19 (coronavirus) global pandemic will have a large negative impact on the Kenyan economy. Even before being affected by the novel coronavirus, Kenya's economy had decelerated. The World Bank estimates that GDP growth in 2019 was about 5.6 percent, down from 6.3 percent in 2018. The COVID-19 (coronavirus) shock is expected to further reduce growth in 2020 with large impacts on services (transport, retail trade, tourism, events, leisure, etc.), industry (manufacturing and construction), and agriculture. The health system is facing an unprecedented challenge to contain the spread of COVID-19 (coronavirus) and care for the infected. In addition, measures taken to slow down the rate of infection, including home confinement, travel restrictions, the closure of schools and entertainment spots, the suspension of public gatherings and conferences, and a nightly curfew, are expected to affect both production and consumption across the economy.